Rhodium(II)-Catalysed Intramolecular O-H Insertion of alpha-Diazo-gamma-Azido-delta-Hydroxy-beta-Ketoesters: Evidence for a Novel Sigmatropic Rearrangement of an Allylic Azide Intermediate - Padwa,Albert (1999)
The Rh2(OAc)4 catalyzed intramolecular O-H insertion reaction of delta-hydroxy-alpha-diazoesters affords 3(2H)-furanone-2-carboxylates in good yield but with moderate selectivity (d.e. ca 60%). The initially formed 2,5-substituted cis-furanones were found to epimerize to the corresponding 2,5-trans isomers when subjected to silica gel chromatography. The Rh2(OAc)4 catalyzed decomposition of gamma-azido-delta-hydroxy-alpha-diazoesters also furnished 3(2H)-furanone-2-carboxylates. These compounds are derived by a sequential O-H insertion reaction followed by a concerted [3,3]-sigmatropic shift of the allylic azide intermediate.